Optimization of Polypropylene Waste Content in Dry-Mix Hot Mix Asphalt Using Polynomial Regression - Amy Wadu; Mateus Sodanango; Obed Nenobais (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2026)
Polypropylene (PP) plastic waste is a serious problem in Indonesia due to the high volume of poorly managed plastic waste, while, on the other hand, road pavements often suffer damage due to traffic loads and extreme weather. The solution to overcome this problem is to optimize the use of PP waste in Hot Mix Asphalt (HMA) mixtures using a dry method to improve the structural performance, flexibility, and durability of road pavement while utilizing plastic waste. A factorial experimental design was applied to four levels of PP percentage to the total aggregate weight, namely 0%, 2.5%, 5%, and 7.5%. Each mixture sample was prepared according to the SNI 06-2489-1991 procedure, then tested using the Marshall method to determine the stability and flow values. The volumetric parameters of Voids in Mix (VIM), Voids in Mineral Aggregate (VMA), and Void Filled Asphalt (VFA) were also measured to evaluate the pore structure and inter-aggregate bonding. The test results showed an increase in stability values to more than 800 kg and an increase in VFA values with the addition of PP, indicating an increase in cohesion and deformation resistance. Meanwhile, VIM and VMA decreased but remained within the permitted specification range (VIM 3–5% and VMA ?15%). Polynomial regression analysis identified that a PP percentage of 6.47% provided the optimal combination of stiffness and flexibility: average stability of 954,41 kg, average flow of 3.1 mm, VIM of 4.2%, VMA of 16.3%, and VFA of 74.3%. Thus, the use of 6.47% PP waste is recommended as the optimum content in dry-mix asphalt. This approach not only supports the principles of circular economy and waste management but also improves the technical performance of road pavements.